(3GdCQHYhf MOjKGs - (3GdYGedj, TeS GdOjf, GdTgjO GdChd, GdTgjO GdChd, eMeO Hf ecj Hf eMeO, J (B786(3g` (B1384(3es ((3eMeO EHQGgje Hf eMeO Jbjs)
(3ChdgG (B:s
(3ChdgG(B: (3deG cKQJ YfGjI GdYdeGA hGdaVdGA GdeJbOejf HLeY CQHYjf MOjKG (B... (3aQCjJ Cf CcKQ GdCTjGA faYG hCgegG GdYHGOGJ GdTQYjI dYdhe GdHdhi HgG hTOI GdMK YdjgGs
(3BNQgG (B:s
(3BNQgG(B: (3hef Udi djdI GdKdGKjf ef TgQ QeVGf GKfi YTQI QcYI aj cd QcYI aGJMI GdcJGH hYTQjf eQI bd gh Gddg CMO hjUdj Ydi GdfHj Udi Gddg Ydjg hSde eFI eQI NJe Gddg dg HGdQMeI(B. (3gPG BNQ GdCMGOjK GdCQHYjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 109s
(3GdPQjYI, L (B1: 262s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs